Neutrophil-lymphocyte and hematocrit scoring in acute pancreatitis as an early predictor of severity and outcome - R., Satish Kumar; A., Sharath; K., Prajwal R.; K., Supreeth (International Surgery Journal, 2020)
Background: The management of acute pancreatitis (AP) is determined by an accurate assessment of severity of disease. Numerous severity indicators have been described till date, most of which require reassessment after admission and resuscitation. Authors propose a novel indicator, the neutrophil-lymphocyte and hematocrit (NLH) scoring as a predictor of acute pancreatitis at the initial time of diagnosis. NLH may have a role in predicting the length of hospital stay and intensive care unit admission and also to predict adverse manifestations of severe acute pancreatitis (SAP). Methods: A retrospective analysis of 107 patients done who diagnosed with acute pancreatitis based on Atlanta 2012 definitions, who were admitted and treated between August 2018 and November 2019. NLH score calculated by adding NLR (neutrophil lymphocyte ratio) and Ht (hematocrit) i.e., NLH=NLR+Ht. NLH was also compared with APACHE II score as a standard predictor of prognosis in acute pancreatitis. Results: Median NLH score among the severe group is significantly higher compared to mild and moderate group. NLH score significantly correlated with length of hospital stay and also had a statistically significant correlation with ICU stay. NLH scoring is comparable with APACHE II scoring system in predicting prognosis in acute pancreatitis. Conclusions: NLH score can be used as a predictor of severity of acute pancreatitis, right at the time of initial diagnosis. Further it may predict adverse outcomes, need for ICU care as well as the length of hospital stay. NLH score can be used as a tool to refer at risk patients to tertiary center needing ICU admission.